Legend of the fin-back whale crest of the Haidas, Queen Charlotte' s Island, B.C. [electronic resource] - Deans, James, 1827-1905. ([S.l. : s.n., 1892)
Signed: James Deans. From: The Journal of American folk-lore, v. 5 no. 16, Jan.-Mar. 1892. Caption title. Electronic reproduction. Mode of access: Internet. 44